2009
DOI: 10.1007/s10995-009-0471-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pre-Conception Health Care: Evaluation of a Social Determinants Focused Intervention

Abstract: The purpose of this study was to evaluate the outcomes of the social determinants component of a multiple determinants model of pre- and inter-conception care. Health department vital statistics and infectious disease data on birth and factors influencing birth outcomes were analyzed for participants in a program designed to mitigate the effects of social class and stress in contrast to a matched comparison group and other relevant populations. The program showed promising results related to reducing infant mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…The social determinants model emphasizes the powerful influences of lifestyle and the conditions in which people live and work. [3][4][5] Prenatal case management seeks to address social determinants through a range of strategies including psychosocial, nutritional, and health promotion assessment; counseling and referral to public health and social services; and overall care coordination. Several evaluation studies of regional or statewide prenatal case management programs have demonstrated reduction of low birthweight or preterm births among Medicaid recipients after program implementation.…”
Section: Introductionmentioning
confidence: 99%
“…The social determinants model emphasizes the powerful influences of lifestyle and the conditions in which people live and work. [3][4][5] Prenatal case management seeks to address social determinants through a range of strategies including psychosocial, nutritional, and health promotion assessment; counseling and referral to public health and social services; and overall care coordination. Several evaluation studies of regional or statewide prenatal case management programs have demonstrated reduction of low birthweight or preterm births among Medicaid recipients after program implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal health is one global health challenges that exhibits dramatic health inequities. Most of the 385,000 maternal deaths occurring each year are concentrated in poor and vulnerable populations and are all the more tragic for being mostly preventable [27]. Maternal health is receiving increased attention in global health, development and human rights agendas and represents a priority area for accelerating progress on the MDGs.…”
Section: Discussionmentioning
confidence: 99%
“…Early evaluations demonstrate successful risk reduction with improved family planning and reduced STDs for program participants and marginally statistically significant improvements in low birth weight (Biermann et al 2006;Livingood et al 2010). Additional research is needed to determine the impact of social and health interventions beginning before pregnancy.…”
Section: Early Intervention Studiesmentioning
confidence: 99%